2001
DOI: 10.1113/eph8602212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbonic Anhydrase Inhibition on the Responsiveness of Laryngeal Receptors in Cats to CO2

Abstract: The effects of carbonic anhydrase inhibition on the responsiveness to CO 2 of pressure-sensitive laryngeal receptors were examined in anaesthetised, paralysed cats. Laryngeal CO 2 -sensitive receptors from the superior laryngeal nerve were selected by their responsiveness to intralaryngeal pressure and to perfusion of solution equilibrated with 9 % CO 2 . The carbonic anhydrase inhibitor, methazolamide, when given intralaryngeally at 10 _4 M, diminished or abolished the responses to the CO 2 -equilibrated solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The mechanisms of the action of CO 2 on laryngeal receptors are not clear, but it would be expected that acidification of the receptor cell or its microenvironment would be responsible. The fact that the CO 2 sensitivity of laryngeal receptors appears to be diminished or abolished by carbonic anhydrase inhibition (Wang, 1994; Coates et al 1996) supports this hypothesis. In the present study, it was shown that the responses of CO 2 ‐sensitive fibres to two hypercapnic solutions with the same P CO2 but different pH values were similar in both direction and magnitude.…”
Section: Discussionmentioning
confidence: 76%
“…The mechanisms of the action of CO 2 on laryngeal receptors are not clear, but it would be expected that acidification of the receptor cell or its microenvironment would be responsible. The fact that the CO 2 sensitivity of laryngeal receptors appears to be diminished or abolished by carbonic anhydrase inhibition (Wang, 1994; Coates et al 1996) supports this hypothesis. In the present study, it was shown that the responses of CO 2 ‐sensitive fibres to two hypercapnic solutions with the same P CO2 but different pH values were similar in both direction and magnitude.…”
Section: Discussionmentioning
confidence: 76%